Pelajaran Dakwah dari Perjalanan dan Sejarah Dakwah Nabi Nuh AS dalam Surat Nuh - Ahmad Adnan (STID DI AL-HIKMAH, 2016)
God sent Noah to guide his people realize as religious duties. And Allah sent down His revelation in order to be used as a guide to practice it. It's all because unfortunately God told them to return to God and to His Heaven, and for those who disbelieve who would deny his back to hell. Noah had to fulfill the task as well with sacrifice and using various uslub (methods), approach to feelings, social, cultural, intellectual and logical, yet little is faithful mad'u attitude and mostly pagan, and ultimately destroyed the infidels and the believers won.